Ang Malolo an analysis of an Ilonggo concept. - Bartonico, Alora Grace Patano (2010.)
This paper examines the different perspectives that have been used to define the meaning of Ilonggo concept malolo. It argues that the concept malolo derives not only its linguistic characteristics but it is also manifested through observable behaviors of Ilonggos. It reviews the meaning of the concept across history by inspecting some pieces of Ilonggo literature of the 20th century. This paper alos examines the meaning of the term as it is understood by today's speakers themselves. It describes the use of the term malolo as a stereotype for Ilonggos by both Hiligaynon and non-Hiligaynon speakers. It observes that the concept has diffeent use and meanings across generations; as well, the understanding of the concept differs from rural and urban areas.
Research Paper (Undergraduate, Bachelor of Arts in History-Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Malolo -- behavior